(untitled) (Research, Society and Development, 2020)
Objective: To describe the clinical and histological aspects, as well as to discuss the diagnosis, treatment and preventive measures of actinic cheilitis (AC). Methodology: A literature review was carried out through the collection of articles indexed in the PubMed, Scielo and Regional Portal of the Virtual Health Library databases in the period 2002 to 2020, in addition to books on Oral Pathology and Stomatology. Results: It is important that, in dental practice, the professional is properly trained, especially the dental surgeon, as it is up to him the role of prevention, diagnosis, treatment and preservation of this clinical condition, with the necessary knowledge for this type of disease , because apparently simple lesions can potentially respond to progression to cancer. Conclusion: To prevent AC, the use of wide-brimmed hats and lip balm with sunscreen is recommended. The ideal treatment should be chosen according to the individual situation of each patient, and for acute AC prevention and conservative treatment is the best option, for chronic AC, total removal of the lesion is necessary.